Simple synthesis of CeFeO3 nanostructures as an efficient visible-light-driven photocatalyst in degradation of Congo red dye: Mechanism investigation. (1st February 2023) - Ahmad, Hunar Aziz; Ahmed, Sangar S.; Amiri, Omid
Abstract: Owing to the extreme water contamination from effluent dyes, finding a suitable and efficient dye degradation technology is needed for the protection of human health and the natural environment. In this work, CeFeO3 Nanocatalyst was prepared by the microwave method with different power, time, and calcination temperatures. Under visible light, the CeFeO3 nanocatalyst was examined for its photocatalytic activity for degradation of Congo red using XRD, SEM, EDS, TEM, DRS, and BET techniques. We also investigated the effect of various parameters on Congo red degradation, including pH, dye concentration, calcination temperature, and photocatalyst dose. The photocatalytic activity results showed that CeFeO3 nanostructures have excellent performance in the degradation of Congo red in visible light. The mechanism behind the degradation of Congo red by CeFeO3 nanostructures reveals that hydroxyl radicals play the main role in the degradation of Congo red. Highlights: CeFeO3 nanostructures were prepared by simple microwave method. CeFeO3 nanostructures show excellent photocatalytic activity under visible light. Mechanism of degradation of Congo red by CeFeO3 nanostructures were conducted.